Fulfill the Requirements of Financial Authority For Adoption Of Financial statements in determining The Tax Base: بحث تطبيقي في الهيئة العامة للضرائب لعينة من الشركات المحدودة (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The Financial authority is considered as one of  the most of benefited parts from financial statements  which depends on it in process of accounting  in taxes as basis to determine The Tax Base , but no confidence from financial authority part in objectivity of income financial information in them for many of limited companies led to no dependence on them to specify taxation contain & dependence on yearly regulations that issued them. To enhance the confidence of financial authority to these lists must meet its requirements, because the menus Fulfill the requirements of the financial authority increases the confidence in these statements and therefore reliable in determining the tax base. So this research aims to specify basic requirements of financial authority that it should be depended by presented financial statements from limited companies, that may enhance role of these statements in process of taxation accounting as a basis to specify The Tax Base.